Destroying necessity with necessity – on László Krasznahorkai's Satantango. Issue 5 (4th May 2022) - Frantzen, Mikkel Krause
ABSTRACT: In this article, I read and analyse the novel Satantango (1985) by the Hungarian writer László Krasznahorkai's. Set in a small community in rural Eastern Hungary – before the fall of the Berlin Wall and the end of the Soviet regime – where the rain is falling incessantly, all hope has been lost, history has ended before it even began, and the houses are crumbling from the inside out, the novel is, for obvious reasons, often considered to have a tone of brutal and bleak pessimism. Robert Boyers thus talks about Krasznahorkai's 'pessimistic virtuosity' and literary realism, the sole purpose of which is disillusion. In this article, however, I would like to contest this claim and look for some paradoxical glimpses of hope hidden in the anatomy of hopelessness that the author undoubtedly makes manifest trough a radical materialism; a hope against hope. I argue that Krasznahorkai destroys necessity with necessity. To that end I will bring in the work of Ernst Bloch as well as Jacques Ranciére's book on filmmaker Bela Tarr who has adapted several of Krasznahorkai's novels for the screen.